2011
DOI: 10.1177/0149206310394863
|View full text |Cite
|
Sign up to set email alerts
|

Management Theory Applications of Prospect Theory: Accomplishments, Challenges, and Opportunities

Abstract: The authors review management research drawing on prospect theory, focusing primarily on studies in strategic management and organizational behavior/human resource management. These studies have made valuable contributions to several prominent research streams. However, they commonly underutilize or misconstrue central arguments from prospect theory. Furthermore, they illustrate that applying prospect theory in organizational settings poses several theoretical and methodological challenges. Thus, the authors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
19

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(169 citation statements)
references
References 158 publications
(189 reference statements)
5
142
0
19
Order By: Relevance
“…Hence, risk perceptions change depending on whether the action, as compared to the reference point, is seen as a pursuit of gain or as loss mitigation (Kahneman and Tversky 1979). Empirical tests of prospect theory predictions have shown that people are more willing to bear risk in loss mitigation than in pursuit of gain (Holmes, Bromiley, Devers, Holcomb, and McGuire 2011;Levy 1992;Plous 1993). Translated into everyday practice, this means that losses loom large in decision-making, and people go to great lengths to avoid or recover a loss, even when doing so involves substantial risk.…”
Section: Theory 21 the Formation Of Entrepreneurial Intentmentioning
confidence: 99%
“…Hence, risk perceptions change depending on whether the action, as compared to the reference point, is seen as a pursuit of gain or as loss mitigation (Kahneman and Tversky 1979). Empirical tests of prospect theory predictions have shown that people are more willing to bear risk in loss mitigation than in pursuit of gain (Holmes, Bromiley, Devers, Holcomb, and McGuire 2011;Levy 1992;Plous 1993). Translated into everyday practice, this means that losses loom large in decision-making, and people go to great lengths to avoid or recover a loss, even when doing so involves substantial risk.…”
Section: Theory 21 the Formation Of Entrepreneurial Intentmentioning
confidence: 99%
“…Recent research into the crisis response strategies of organisations has created some theoretical foundations for analysing the relation between risk preferences and strategic decision-making on a corporate level, with the main goal being to supplement existing rational analytical models (Holmes et al, 2011). Evidence indicates that there is a relation between risk perception in the context of opportunity and threat and the type of strategic responses to a crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, strategic judgment significantly influences the strategic orientation of organisations (Holmes et al, 2011), while the orientation of the strategic decision maker, i.e. the managerial perception of opportunities and threats, influences the choice of organisational strategy (Devers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PT 1992, in turn, extends the celebrated concept of original prospect theory (=OPT 1979) by Kahneman and Tversky (1979) to the case of several possible gain values in a way that satis…es …rst-order stochastic dominance. In a recent review on applications of OPT 1979 and PT 1992 (in their terminology, PT and CPT, respectively) in management science, Holmes, Bromiley, Devers, Holcomb, and McGuire (2011) write:…”
Section: Related Literature and Further Motivationmentioning
confidence: 99%
“…More than 550 articles citing either of these two studies (or both) have appeared in periodicals consistently recognized as top academic journals for management research [:::]."(p. 1079) Holmes et al (2011) proceed to list applications of OPT 1979 and PT 1992 to management science, including executive compensation, negotiations, a¤ect and motivation, human resource management, organizational risk and return, and …rm risk-taking behavior. Despite the huge popularity of OPT 1979 and PT 1992 as alternatives to EU theory in applications, the present paper is, to the best of my knowledge, the …rst mathematically rigorous approach for addressing the question of whether the non-additive decision weights of OPT 1979 and PT 1992 (in my context: the non-additive probability measures of CEU theory) will reduce through Bayesian learning to the additive probabilities of EU theory or not.…”
Section: Related Literature and Further Motivationmentioning
confidence: 99%